Schwannomas at unusual locations: a case series - Pachal, Sumitava; Chatterjee, Sudipta; Chaki, Supratim (International Journal of Research in Medical Sciences, 2024)
Schwannoma, also known as neurinoma or neurilemmoma, is a benign, encapsulated, slow-growing, peripheral nerve sheath tumor arising from the Schwann cells. They are seen mostly in the head and neck region, with the 8th cranial nerve being the most common site. There it is known as vestibular Schwannoma or acoustic neuroma. It is usually seen in 20–50 years of age, with no specific sex or racial predilection. Histopathologically, there may be compact hypercellular Antoni A areas and myxoid hypocellular Antoni B areas. Nuclear palisading around fibrillary processes, also known as Verocay bodies, is often seen in cellular areas. In this article, we present a series of cases where all of the patients presented to us with soft tissue swelling for varying periods of time in different locations, mostly in extremities. Cytopathology and radiology couldn’t come to a specific diagnosis. The tumors were excised en mass. The post-operative histology of the excised tumor confirmed the diagnosis of Schwannoma, arising from peripheral nerve sheath. There was no recurrence after follow up for 1 year. Schwannomas most commonly arise from the peripheral nerve sheaths usually at the head neck region. They are seen rarely in other peripheral nerves. They should be excised en mass with intact epineurium. After complete excision their recurrence rate is very low thus having a good prognosis.